1980
DOI: 10.1111/j.1748-1716.1980.tb06579.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polycythemia on blood flow in working and non‐working skeletal muscle

Abstract: The effect of acutely induced polycythemia on blood flow and viscosity in the vasodilated vascular bed of working and non-working skeletal muscle was studied. In 12 mongrel dogs anesthetized with thiopental sodium the calf muscle of one hind limb was isolated. Vasodilation was induced either by sciatic stimulation setting the muscle at maximal work or by i.a. infusion of papaverine. Blood flow was measured at different perfusion pressure before and after infusion of 300 ml packed homologous red cells. Blood vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
4
15
1
Order By: Relevance
“…A similar flow-preserving effect has been shown to exist after acutely induced polycythemia (Gustafsson et al, 1980). A high hematocrit was found to be more deleterious to the oxygen availability in the resting muscle than in the exercising muscle.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…A similar flow-preserving effect has been shown to exist after acutely induced polycythemia (Gustafsson et al, 1980). A high hematocrit was found to be more deleterious to the oxygen availability in the resting muscle than in the exercising muscle.…”
Section: Discussionsupporting
confidence: 63%
“…1), the surgical preparation being similar to the one described in a previous study (Gustafsson et al, 1980). The thigh muscles were divided above the knee joint, as were all vessels except the popliteal artery and vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas viscosity rises in a curvilinear fashion with increasing polycythemia, cardiac output falls in a much more linear fashion (3,22). Similar falls in cardiac output occur both at rest and with exercise during polycythemia even though viscosity changes are minimized in exercising muscle beds (10,22). Finally, several studies have shown that exercise capacity and maximal oxygen uptake may not fall with polycythemia as had been previously described (12,22).…”
mentioning
confidence: 75%
“…An increase in hematocrit from 46-61 % should not per se decrease flow more than about 40-50% as evident from other studies concern ing relationships between hematocrit and pressure-flow curves in skeletal muscle prep arations [4,11,15,17]. It therefore seems that the hypotensive state contributes to the pronounced changes in vivo, possibly by plugging of the microvascular bed.…”
Section: Discussionmentioning
confidence: 50%